The Effect Of Taro Flour Substitution On The Quality Of Mekar Steamed Sponge - Rahmatika, Aghisyna; Syarif, Wirnelis (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
Mekar steamed sponge is an Indonesian cake made from wheat flour, sugar, eggs, and other ingredients which are stirr and then cooked using steaming technique. The addition of taro flour as a substitute for wheat flour in the manufacture of mekar steamed sponge is expected to vary and improve the quality of the mekar steamed sponge. Taro flour is high in nutrition, low in fat, low in calories and easy to digest starch content. This study discusses the analysis of the effect of taro flour substitution on the quality (volume, shape, color, aroma, texture and taste) of mekar steamed cake with the substitution of taro flour as much as 15%, 25%, and 35%. This type of research is a pure experiment with a completely randomized design method (CRD) with three treatments and three repetitions. The data used is primary data obtained directly from 5 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of the taro flour mekar steamed sponge cake. The data that has been obtained is then tabulated in tabular form and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount Ftable, then it is continued with Duncan's test. The results of this study indicate that there is an effect on the bloom volume, neat shape, white color, and fine porous texture. Based on the results of the study, the best results were found in the treatment (X₁)15%.